Keunggulan Bersaing dan Loyalitas Pelanggan pada Distribusi Impor Beras Khusus di Indonesia - Ayu, Rifana; Rahardjo, Sri; Tantri, Francis; Adi, Erman Noor; Kania, Dinar Dewi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
Importing the specific rice could only be done by BUMN (Badan Usaha Milik Negara) which in this article represented by PT DFG. The company is still lack of supervision of the customer relationship management implementation due to the absence of the special department and also lack of supervision of distribution. The study used Path Analysis with 35 distributor companies as sample. The purpose of the research is to analyze, directly and indirectly, the variables of customer relationship management and supply chain management on customers’ loyalty of imported specific rice intervened by competitive advantage variables. The results of the study show that the competitive advantage cannot act as an intervening variable and has an indirect effect on customer relationship management of the rice commodity customers’ loyalty. On the other hand, the competitive advantage can act as an intervening variable and has an indirect effect on supply chain management of the specific rice customers’ loyalty. Thus, the changes of the supply chain management implementation in PT DFG can affect customers’ loyalty indirectly through competitive advantage.